Religiusitas Dalam Puisi “Sergius Mencari Bacchus” Karya Norman Erikson Pasaribu: Religiusitas Dalam Puisi “Sergius Mencari Bacchus” Karya Norman Erikson Pasaribu - Soewandi, Adinda (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2023)
Abstract The poem "Sergius Mencari Bacchus" by Norman Erikson Pasaribu which is the object of this research aims to describe things related to (1) the physical and mental structure of the poem "Sergius Mencari Bacchus", (2) aspects of Christian religiosity in the poem "Sergius Mencari Bacchus”. The data collection technique was based on the form of a part of one of the poems in the poetry anthology book "Sergius Mencari Bacchus". The analysis technique used is in the form of analysis and interpretation of the data which is the subject of the study, as well as the emphasis on analyzing the religious values ​​contained therein. The results of the study describe that there are six physical structures and four mental structures that are builders in the poem "Sergius Mencari Bacchus". There is also an explanation regarding each stanza in the poem "Sergius Mencari Bacchus" in relation to the value of Christian religiosity. With the research that has been done, new meanings and understandings have been found regarding the values ​​of Christian religiosity which are very strong in the poem. How can Indonesian society, which is predominantly Muslim, be unable to interpret the poem "Sergius Mencari Bacchus" and its relation to the history that happened to the two figures who are the object of the poem. Apart from being related to religious values, there are also historical values ​​that lie behind the story of the two figures. Keywords: christianity, poetry, religiosity, inner structure, physical structure Abstrak Puisi “Sergius Mencari Bacchus” karya Norman Erikson Pasaribu yang menjadi objek penelitian tersebut bertujuan untuk mendeskripsikan hal-hal terkait (1) struktur fisik dan batin puisi “Sergius Mencari Bacchus”, (2) aspek-aspek religiusitas Kristen dalam puisi “Sergius Mencari Bacchus”. Teknik pengumpulan data berdasar pada wujud bagian salah satu puisi dalam buku antologi puisi “Sergius Mencari Bacchus”. Teknik analisa yang digunakan berupa analisa dan juga pemaknaan terhadap data yang menjadi subjek kajiannya, serta penekanannya pada analisa nilai religiusitas yang terkandung didalamnya. Hasil penelitian menjabarkan adanya enam struktur fisik serta empat struktur batin pembangun dalam puisi “Sergius Mencari Bacchus”. Terdapat juga penjabaran terkait tiap bait dalam puisi “Sergius Mencari Bacchus” dalam kaitannya dengan nilai religiusitas Kristen. Dengan adanya penelitian yang telah dilakukan ditemukan pemaknaan dan pemahaman baru terkait nilai religiusitas Kristen yang sangat kental dalam puisi tersebut. Bagaimana dalam masyarakat Indonesia yang mayoritas beragama Islam kurang dapat memaknai puisi “Sergius Mencari Bacchus” serta kaitannya dengan sejarah yang terjadi pada dua tokoh yang menjadi objek dari puisi tersebut. Selain terkait dengan nilai religiusitas terdapat juga nilai sejarah yang melatar belakangi penceritaan dua tokoh tersebut. Kata kunci: kristen, puisi, religiusitas, struktur batin, struktur fisik